Efektivitas Sistem Jaringan Dokumentasi DanInformasi Hukum (Sjdih) DiDaerah Istimewa Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT This paper describes the implementation of Law Information and Documentation System on Government of Yogyakarta Special Territory base on the Man Power Capability (X1) technology (X2), organization climate (X3), commitments of group member (X4) and leadership style (X5). The results show that man power capability (XI) does not influence significantly to effectiveness, while technology (X2), organization climate (X3), commitments of group member (X4) and leadership style (X5) have influence on effectiveness significantly although in the range of low to middle value. Leadership style (X5) of the leader in the Documentation and Information Network System (DINS) unit through analysis